2012
DOI: 10.1111/imr.12019
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the resting TCR in nanoscale oligomers

Abstract: Despite the low affinity of the T-cell antigen receptor (TCR) for its peptide/major histocompatibility complex (pMHC) ligand, T cells are very sensitive to their antigens. This paradox can be resolved if we consider that the TCR may be organized into pre-existing oligomers or nanoclusters. Such structures could improve antigen recognition by increasing the functional affinity (avidity) of the TCR-pMHC interaction and by allowing cooperativity between individual TCRs. Up to approximately 20 TCRs become tightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 64 publications
4
83
2
Order By: Relevance
“…Ligand binding is thought to induce clustering of many cell surface receptors, including EGFR, T cell receptors, Ephrin receptors, and Toll-like receptors (33,34,61,62). Receptor clustering is dependent on many aspects, such as ligand affinity, ligand dissociation, the size of ligands, and the concentration of coactivators (63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Ligand binding is thought to induce clustering of many cell surface receptors, including EGFR, T cell receptors, Ephrin receptors, and Toll-like receptors (33,34,61,62). Receptor clustering is dependent on many aspects, such as ligand affinity, ligand dissociation, the size of ligands, and the concentration of coactivators (63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Some aspects of TCR–pMHC molecular interactions that are of current research interest are the frequency of encounters between T cells and the agonist pMHC, how cell–cell interactions determine the activation of lymphocytes (2), how early interactions change the state of the T cell receptor (3), what are the mechanisms of modulation of receptor–ligand interactions at cell–cell interfaces (4), and how protein organization in the cell membrane (for instance, protein islands or lipid rafts) affects the recognition process (5). Some recent experiments have explored the role of dimensionality on T cell activation and have highlighted the significance of the events taking place at the receptor level [see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been suggested that, contrary to what happens in TCR micro-clusters and the immunological synapse, clustering is not only induced by the ligand but by an avidity maturation mechanism (or pre-clustering) (17), allowing the aggregation of chains of TCRs as long as 20 units (around 200 nm long), and referred to as nano-clusters (3, 18). Specifically, multimeric TCR–CD3 complexes are activated at low agonistic pMHC concentrations and monomeric TCRs remain unaffected at low ligand concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans and other mammals, the TCR signaling complex comprises eight type-I membrane-spanning polypeptides that include the TCR ␣␤ heterodimer, the CD3⑀␥ and CD3⑀␦ heterodimers, and the CD3 homodimer (1), although higher order molecular assemblies are considered to exist (2,3). The ␣␤TCR functions to recognize peptide-, lipid-, and vitamin B precursor-based antigens that are presented by major histocompatibility complex (MHC) or MHC-like molecules (4 -7).…”
mentioning
confidence: 99%